Daya terima dan zat gizi almond crispy coklat sebagai camilan alternatif berserat tinggi [Acceptability and nutrient content of chocolate crispy almond as an alternative high fiber snack] - Evajune Widiyawati; Nani Ratnaningsih; Badraningsih Lastariwati (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2021)
This study aimed to determine the acceptability of the product and the nutritional content of the chocolate crispy almond product. This study used the Research and Development (R&D) method with a 4D model (define, design, development, disseminate). Data analysis used descriptive statistics and presented in the form of mean and standard deviation. The sensory test involved 50 panelists from the general public, while the nutritional content was carried out in the laboratory. The results showed that as many as 83% of consumer acceptance of crispy almond products was at a score of 3.30 (likes). Laboratory test results showed that crispy almond products contain 4.30% water, 1.30% ash, 10.62% protein, 19.03% fat, 46.37% carbohydrates, 396.05kcal energy, and total fiber content of 18.39%. Based on this high fiber content, crispy almond products can be categorized as fiber-rich snacks.